Penguraian Masalah Banjir di Kampung Akrilik, Kelurahan Gunung Pangilun, Padang - Nurhamidah Nurhamidah; Muhammad Rifki Halim (Warta Pengabdian Andalas, 2023)
Along with the increasing number of residents every year, the higher the cost of constructing houses or buildings. The high number of developments every year requires attention from the community or project owners to pay attention to matters regarding water catchment areas. We often see buildings or housing covering the drainage channels underneath for access in and out of the building without making control tanks or openings for cleaning the drainage channels; sometimes, some reduce the width of the drainage. The lack of water catchment areas and drainage channels will cause flooding if it rains continuously. Therefore, a survey was conducted regarding the causes of the flooding that occurred in Acrylic Village, Gunung Pangilun Village, through the Humanitarian Project MBKM program. With the survey of the village, it was known what causes the flooding in the village; then, a solution was planned to solve this problem scientifically.